THE INFLUENCE OF MARKETING MIX STRATEGY AND SERVICE QUALITY ON CUSTOMER DECISIONS IN THE ELECTRICITY POWER UPGRADE PROGRAM WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT PLN UP3 SOFIFI - Didit Sujatmoko; Hadiah Fitriyah (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study investigates the influence of marketing mix strategy and service quality on customer decisions to participate in the electricity capacity upgrade program at PLN UP3 Sofifi, with customer satisfaction serving as a mediating variable. Method: A quantitative research design was employed using a survey of 100 PLN customers. Data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess both direct and indirect relationships among variables. Results: Findings indicate that marketing mix strategy and service quality significantly and positively affect customer decisions, both directly and indirectly through customer satisfaction. Effective marketing strategies—comprising appropriate product offerings, competitive pricing, engaging promotions, and accessible service locations—enhance satisfaction and decision-making. Similarly, service quality dimensions such as reliability, responsiveness, assurance, empathy, and tangibility contribute positively to these outcomes. Novelty: This study provides empirical evidence on how customer satisfaction mediates the relationship between marketing strategy and service quality in the context of public utility services, offering practical insights for PLN in optimizing marketing efforts and service delivery to increase customer participation in capacity upgrade programs.